Ending the Other Arms Race: An Argument for a Ban on Assault Weapons - Abrams, Daniel (2015)
The most enduring images of the recent Los Angeles riots featured weapons. Guns were, it seemed, everywhere and in the hands of everyone. Rioters and shopkeepers, looters and police: all were armed. More weapons are on the way. In the first eleven days of May, Californians responded to the riots by purchasing over 20,000 guns